On the Inevitability of Aging: Essentialist Beliefs Moderate the Impact of Negative Age Stereotypes on Older Adults' Memory Performance and Physiological Reactivity. (20th July 2016) - Weiss, David
Abstract: Objectives: The goal of this research was to investigate how individual differences in essentialist beliefs about aging affect how older adults' respond to negative age stereotypes. Essentialist beliefs about aging (EBA) define the process of aging as fixed and inevitable rather than malleable and modifiable. Method: Two experiments including older adults tested the hypothesis that EBA moderate the effect of negative age stereotypes on older adults' memory performance and physiological reactivity. Results: In line with predictions, results of Experiment 1 ( N = 79, 61–87 years) showed that for older adults with strong EBA, the activation of negative age stereotypes (vs neutral information) led to stereotype assimilation entailing a poorer memory performance. In contrast, for older adults with non-EBA, the activation of negative age stereotypes led to stereotype reactance entailing a better memory performance. Experiment 2 ( N = 41; 65–92 years) replicated this pattern and also showed that older adults who endorsed rather than rejected EBA exhibited increased systolic blood pressure reactivity when negative age stereotypes were activated. Discussion: The discussion focuses on pathways through which age stereotypes impact cognitive performance and health in later adulthood, as well as ways to stimulate positive plasticity by changing EBA.